Analisis Keaktifan Siswa pada Organisasi Siswa Intra Sekolah dalam Meningkatkan Prestasi Belajar Siswa - Iqbal, Muhammad; Suhardi, Muhamad; Deanti, Ramadani Triana (Universitas Pendidikan Mandalika, 2024)
Abstract: This study aims to find out: 1) a description of student activity in the Intra-School Student Organization (OSIS) at SMPN 3 Mataram, 2) a description of student achievement at SMPN 3 Mataram, 3) the effect of activeness on the Intra-School Student Organization (OSIS) on student achievement at SMPN 3 Mataram. The research approach used is quantitative, with a sample of 69 students who are members of the Student Council. Data collection was carried out using documentation and questionnaire techniques. The collected research data were then analyzed using descriptive statistical techniques and simple regression, to test the research hypothesis. The results of the analysis show: 1) Based on the results of the correlation test, the value of r-count (0.036) > r-table (0.001) is obtained, which means that there is an insignificant relationship with a moderate level between the variables of student activity and learning achievement; 2) The resulting regression equation Y = 82.046 + 0.258 (X); 3) The effect of student activeness (X) on learning achievement (Y) is an insignificant effect, based on t-test = 0.297 with a significance level of 0.768; 4) The results of the F test show the value of F-count = 0.088 with a significant level of 0.768 which means that the prediction of student learning outcomes using student activity is not an accurate prediction; and 5) Based on the test of the coefficient of determination, the value of R = 0.036 can be interpreted that there is a large influence of student activeness on learning achievement which is 3.6%.Keywords: Student Activeness, Intra-School Student Organization (OSIS), Learning AchievementAbstrak: Penelitian ini bertujuan untuk mengetahui: 1) gambaran keaktifan siswa pada OrganisasiÂ Siswa Intra Sekolah (OSIS) di SMP Negeri 3 Mataram, 2) gambaran prestasi belajar siswa di SMP Negeri 3 Mataram, 3) pengaruh keaktifan pada OrganisasiÂ Siswa Intra Sekolah (OSIS) terhadap prestasi belajar siswa di SMP Negeri 3 Mataram. Pendekatan penelitian yang digunakan yaitu kuantitatif, dengan sampel 69 siswa yang merupakan anggota OSIS. Pengumpulan data dilakukan dengan menggunakan teknik dokumentasi dan angket. Data penelitian yang terkumpul kemudian dianalisis dengan menggunakan teknik statistik deskriptif dan regresi sederhana, untuk menguji hipotesis penelitian. Hasil analisis menunjukkan: 1) Berdasarkan hasil uji korelasi, diperoleh nilai r-hitung (0,036) > r-tabel (0,001), yang berarti bahwa terdapat hubungan yang tidak signifikan dengan taraf sedang antara variabel keaktifan siswa dengan prestasi belajar; 2) Persamaan regresi yang dihasilkan Y = 82,046 + 0,258 (X); 3) Pengaruh Keaktifan Siswa (X) terhadap Prestasi Belajar (Y) merupakan pengaruh yang tidak signifikan, berdasarkan nilai t-hitung = 0,297 dengan taraf signifikansi 0,768; 4) Hasil uji F menunjukkan nilai F-hitung = 0,088 dengan taraf signifikan 0,768 yang berarti bahwa prediksi terhadap hasil belajar siswa menggunakan keaktifan siswa bukan merupakan prediksi yang akurat; dan 5) Berdasarkan uji koefisien determinasi diperoleh nilai R= 0,036 dapat diartikan adanya besar pengaruh variabel keaktifan siswa terhadap prestasi belajar adalah sebesar 3,6%.Kata Kunci: Keaktifan Siswa, Organisasi Siswa Intra Sekolah (OSIS), Prestasi Belajar